A Chronicle Review of Nonsilicon (Sn, Sb, Ge)‐Based Lithium/Sodium‐Ion Battery Alloying Anodes. Issue 8 (11th May 2020) - Liang, Suzhe; Cheng, Ya‐Jun; Zhu, Jin; Xia, Yonggao; Müller‐Buschbaum, Peter
Abstract: Since the commercialization of lithium‐ion batteries (LIBs) in the early 1990s, tin (Sn), antimony (Sb), and germanium (Ge)‐based anodes have attracted considerable research interest as promising candidates for next‐generation LIBs due to their high theoretical capacities, suitable operating voltages, and natural abundance. Additionally, the awareness of limited global lithium sources promoted the renaissance of sodium‐ion batteries (SIBs) in recent years. Sn, Sb, and Ge can electrochemically alloy with sodium and are regarded as promising anode candidates for high‐performance SIBs. However, these alloying/dealloying anodes suffer severe volume expansion during lithiation or sodiation processes, which is one of the biggest obstacles toward practical applications. In order to solve this problem, several strategies are developed including reducing the absolute size of particles, creating interior void space, and introducing buffer media. After more than two decades' efforts, the electrochemical performance of Sn, Sb, and Ge‐based anodes is significantly improved. Considerable studies about Sn, Sb, and Ge‐based anodes are summarized in a chronicle perspective and the brief development histories of the three anodes are outlined. With this unique review, light will be shed on the future trends of the studies on the Sn, Sb, and Ge‐based anodes for advanced rechargeable batteries. Abstract : A comprehensive review of alloying‐based nonsilicon lithium/sodium‐ion battery anodes over the last few decades is performed. Unique insights about the evolution trends of the studies are revealed, which are instructive and inspiring for the development of high‐performance rechargeable batteries.